IMPROVING STUDENTS' SCIENTIFIC EXPLANATION SKILLS THROUGH POGIL MODEL WITH SOCIOSCIENTIFIC ISSUE CONTEXT - Rahayu, Sri; Aldresti, Fitri; Fajaroh, Fauziatul (Jurnal Pengajaran MIPA, 2018)
Students' must be able to reasons scientifically in understanding our rapidly changing world, in which scientific explanation skill can be defined as an ability to make a reasonable explanation of a phenomenon based on scientific facts as well as forming a relationship based on evidence and logical reasoning. In this study, we examine the development of students' scientific explanation skill through the implementation of POGIL inquiry model with Socio-scientific Issues (SSI) context. A difference in scientific explanation skill after learning was found and implications to chemistry learning are discussed.